Perbedaan Penyembuhan Luka Post Partum Post Sectio Caesarea yang dilakukan Perawatan Luka dengan NaCl 0,9% dan Povidon Iodine 10% di RSUD Tugurejo Semarang Tahun 2013 - Lesia Setyawati; Ida Ariyanti; Sri Wahyuni (S) (JURNAL KEBIDANAN, 2013)
Caesarean sectio rate is increasing dramatically, especially in the end of 20th century. Caesarean sectio is a surgical operation and it should have infection rate lower than 2 percent. Using and choosing not appropriate wound care product will cause longer inflammation time process and less oxygen supply in wound location that will cause longer wound recovery. The purpose of this research was to know the difference of post caesarean sectio wound recovery between NaCl 0,9% wound care in Bougenville room of RSUD Tugurejo Semarang 2013. This research was pre experimental , with post test only control group design. Sample in this research was caesarean sectio post partum with inclusion of criteria as much as 30 respondents with 15 respondent as experiment group and 15 respondents as control group. Processing data using Mann Whitney test resulted p value 0,317 0,05 which mean that there was no difference wound recovery post caesarean sectio between NaCl 0,9% wound care and Povidone Iodine 10% wound care. From the result of this research it is expected to use NaCl 0,9% in wound care of Post caesarean sectio. With different of mean 1,00 the result of this reseach can become a litrature for nex research by using more controlling of confounding variable.